Critical Discourse Analysis of Teun A. Van Dijk's model on @gerindra's TikTok Content in Gaining Gen Z Votes for Prabowo Subianto in the 2024 Election - Anggi Aprilia; Feri Firdaus (LONTAR: Jurnal Ilmu Komunikasi, 2024)
This study aims to outline a critical discourse analysis of ten TikTok contents from @gerindra related to Prabowo Subianto in their efforts to capture Gen Z votes. The high usage of TikTok among Gen Z and its significant role in the 2024 elections, with voting proportions reaching 23%, has substantial implications. This research analyzes the interconnection of discourse and the role of TikTok in the effort to attract Gen Z votes. The study employs Teun A. Van Dijk's critical discourse analysis model, which includes text structure, social cognition, and social context. Data is collected through interviews and categorized based on the research subjects' statements. The subjects reported that in the 2024 elections, Gerindra must adapt to social media trends, particularly TikTok, in order to gain Gen Z support for Prabowo Subianto. This adaptation involves using a "serious yet relaxed" political communication style in their brief, light, and straightforward content. The study finds that Gerindra creates such content to present Prabowo as more humanistic, contrasting with his previously known strict and rigid image.